Evaluation of Shunt Losses in Industrial Silicon Solar Cells. (29th June 2016) - Somasundaran, P.; Gupta, R.
Abstract : Shunting is one of the key issues in industrial silicon solar cells which degrade cell performance. This paper presents an approach for investigation of the performance degradation caused by the presence of ohmic extended shunts at various locations in industrial silicon solar cells. Location, nature, and area of the shunts existing in solar cells have been examined by lock-in infrared thermography (LIT). Based on LIT images and experimental dark I-V curves of solar cell, shunted cell has been modeled, from which loss in fill factor and efficiency due to the specific shunt has been obtained. Distributed diode modeling approach of solar cell has been exploited for obtaining simulation results which were supported by experimental measurements. The presented approach is useful to estimate performance reduction due to specific shunts and to quantify losses, which can help in improving the efficiency of solar cell during production by tackling the shunt related problems based on the level of severity and tolerance.